Patient Experiences with Cardiac Surgery in Alberta, Canada: Results from a Validated Survey - Kemp, Kyle; Santana, Maria; Knudtson, Merril; Paolucci, Elizabeth Oddone; Quan, Hude (International Journal of Population Data Science, 2018)
Introduction Research shows that a better patient experience may be associated with better outcomes. Most investigations, however, have only examined patients’ overall rating of care, which does not identify individual aspects of care which may be improved. Additionally, little is known about the experience of specific clinical groups in acute care. Objectives and Approach The study objective was to examine the experience of patients undergoing cardiac surgery across Alberta. Surveys were completed within 6 weeks of hospital discharge, and linked with inpatient administrative records. Study eligibility was determined using Canadian Classification of Intervention (CCI) procedure codes, to include patients who underwent coronary artery bypass graft (CABG), valve replacement, and/or percutaneous coronary intervention (angioplasty). The survey contained 56 questions and assessed multiple aspects of care. Results for each question were classified as percentage in “top box”, where “top box” represented the best possible result (e.g. nurses “always” explaining things in a way patients could understand). Results From April 2014 to March 2017, 1,921 patients completed a survey following cardiac surgery. This included 1,117 angioplasty only (58.2%), 409 CABG only (21.3%), 308 valve replacements (16.0%) and 87 (4.5%) who underwent multiple procedures. Patients were predominantly male (74.2%), over 50 years of age (88.6%) and admitted to hospital urgently (72.7%). The top three performing questions were nurses treating patients with courtesy and respect (91.4% reporting “always”), receiving written information about symptoms to watch out for after leaving hospital (90.9% “yes”), and discussion with hospital staff about help needed once leaving hospital (90.2% “yes”). The three poorest performing questions were hospital room quietness at night (48.6% “always”), staff describing possible side effects of new medications (51.4% “always”), and hospital room/bathroom cleanliness (64.9% “always”). Conclusion/Implications Our results provide patient-reported feedback about the perceived strengths and areas for improvement associated with cardiac surgery in Alberta. By linking completed surveys with administrative data, we are able to examine the experience of specific clinical groups, while eliminating additional survey burden for patients.